2011
DOI: 10.1038/clpt.2011.110
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study Evaluating Tolerability, Pharmacokinetics, and Preliminary Efficacy of L-Menthol in Upper Gastrointestinal Endoscopy

Abstract: Peppermint oil has been shown to relax gastrointestinal smooth muscle. In this randomized, placebo-controlled study, an L-menthol preparation, NPO-11, was assessed for tolerability and pharmacokinetics (PK) during gastrointestinal endoscopy. Single doses of NPO-11, as high as 320 mg, were well tolerated. NPO-11 was rapidly absorbed, with peak concentrations reached within 1 h after administration. Approximately 70% of the administered L-menthol and its metabolites were excreted in the urine, and this amount fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 24 publications
3
62
0
Order By: Relevance
“…x l-menthol-HP-β-CD (s) → y l-menthol (g) + + z HP-β-CD (s) (2) The rate expression for the disappearance of l-menthol--HP-β-CD in the reaction as shown in Eq. (2) may be expressed by: (3) where α is the fraction of l-menthol-HP-β-CD decomposed at time t, n is the order of reaction, and k is the rate constant.…”
Section: Pyrolysis Kinetic Parameters Of L-menthol-hp-β-cd Inclusion mentioning
confidence: 99%
See 1 more Smart Citation
“…x l-menthol-HP-β-CD (s) → y l-menthol (g) + + z HP-β-CD (s) (2) The rate expression for the disappearance of l-menthol--HP-β-CD in the reaction as shown in Eq. (2) may be expressed by: (3) where α is the fraction of l-menthol-HP-β-CD decomposed at time t, n is the order of reaction, and k is the rate constant.…”
Section: Pyrolysis Kinetic Parameters Of L-menthol-hp-β-cd Inclusion mentioning
confidence: 99%
“…In certain medications, l-menthol is used to treat sunburns, as it provides a cooling sensation. l-menthol is also included in nonprescription products for short-term relief of minor sore throat and minor mouth or throat irritation 3 . Furthermore, l-menthol can reduce incidence rates of a variety of cancers (e.g.…”
Section: Practical Applicationmentioning
confidence: 99%
“…Benowitz et al has reported urine levels of the MG as biomarker of exposure in menthol smokers with an improved method by liquid chromatography–mass spectrometry (54). Other study have reported the assessment of MG in humans related menthol in the treatment of gastrointestinal disease using gas chromatography–mass spectrometry in urine and plasma (53, 55, 56). In this study, by using a robust method UPLC-Q-TOF MS which allows better separation and resolution for the untargeted metabolomics, MG was detected simultaneously with smokers’ metabolomics profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Human plasma levels of intact menthol after oral administration were either not detectable or only in quantities less than 1% of the major metabolite, menthol glucuronide (Gelal et al, 1999;Hiki et al, 2011), suggesting a very efficient first-pass glucuronidation of menthol at the free hydroxyl group by e.g. UDP-glucuronosyltransferase 2B7 (Coffman et al, 1998).…”
Section: Pharmacokineticsmentioning
confidence: 98%